Open Source Implementation of M-Learning for Primary School in Malaysia - Mahamad, Saipunidzam; Ibrahim, Mohammad Noor; Foad , Izzriq Ab Malek; Taib, Shakirah Mohd (World Academy of Science, Engineering and Technology, 2008)
With the proliferation of the mobile device technologies, mobile learning can be used to complement and improve traditional learning problems. Both students and teachers need a proper and handy system to monitor and keep track the performance of the students. This paper presents an implementation of M-learning for primary school in Malaysia by using an open source technology. It focuses on learning mathematics using handheld devices for primary schools’ students aged 11 and 12 years old. Main users for this system include students, teachers and the administrator. This application suggests a new mobile learning environment with mobile graph for tracking the students’ progress and performance. The purpose of this system is not to replace traditional classroom but to complement the learning process. In a testing conducted, students who used this system performed better in their examination.